Citalopram in the treatment of elderly chronic heart failure combined with depression: A systematic review and meta-analysis - Yan, Longmei; Ai, Yuzhen; Xing, Yaxuan; Wang, Biqing; Gao, Anran; Xu, Qiwu; Li, Hongzheng; Chen, Keji; Zhang, Jingchun (Frontiers in Cardiovascular Medicine, 2023)
Background: Depression is an independent factor to predict the hospitalization and mortality in the heart failure patients. As we all know, citalopram is an effective drug for depression treatment . In this work, the effect of citalopram on improving depressive symptoms in heart failure patients was systematically evaluated. Objective: To evaluate the efficacy and safety of citalopram in the treatment of elderly chronic heart failure combined with depression. Methods: PubMed, EMBASE, Cochrane, Web of Science, CNKI, VIP, CBM and Wanfang were searched from their inception to May 2022. Randomized controlled studies of citalopram in the treatment of elderly chronic heart failure combined with depression were included. Independent screening and extraction of data information were conducted by 2 researchers, and the quality was assessed using the Cochrane bias risk assessment tool. Review manager 5.4.1 was employed for statistical analysis. Results: The results of meta-analysis prove that the citalopram treatment for depressed patients with chronic heart failure have a benefit in LVEF (MD: 2.42, 95% CI: 0.51, 4.33) and NT-proBNP (MD : -537.78, 95%CI :-718.03 to -357.54). Moreover, HAMD-24 is improved (MD : -8.52, 95%CI : -10.15 to -6.89). However, the comparison with control group indicates that there is no good effect on LVEDD (MD:-2.80, 95% CI: -4.77 to -0.83), HAMD-17(MD: -5.14, 95%CI: -11.60 to 1.32 and MADRS(MD: -1.57, 95%CI: -3.47 to 0.32). No obvious adverse drug reactions were observed. Conclusion: Citalopram treatment for depressed patients with chronic heart failure has a positive effect on LVEF and NT-proBNP. It can relieve HAMD-24 and GDS, while it still need to verify the relative benefits of LVEDD, HAMD-17 and MADRS.